Selection of Student Housing Types for Universitas Trisakti in DKI Jakarta - Situmorang, Rahel; Supriyatna, Yayat; Yahya, Wisely; Aprianto, Kezia Rianka Putri; Adriana, Martina Cecilia (SPECTA Journal of Technology, 2024)
The large number of students has implications for the need for housing during their studies around the campus area. Students need temporary living conditions in a location as part of the life cycle of young people in the phase of leaving their parents for educational purposes. Many factors result in the diversity of housing typologies needed by students. Fulfilling students' expectations of housing will create comfort and will also affect the performance of the students' studies. Research related to student housing preferences in Jakarta, which is the most densely populated city in Indonesia, is still rare. This research method is quantitative using Questionnaire Technique as data collection. The number of respondents in this study based on the Slovin sampling method is 148 students. This study will be analyzed using statistical methods both descriptively and crosstab. The results of this study identified that most Trisakti students prefer to live in owned houses such as their parents' house, relatives' house, or apartments compared to renting a house close to campus. The crosstab results show that gender, distance from residence, reasons for choosing a residence, and student origin affect the distribution of housing type selection between rental or owned residences. In addition, based on the results of perception, pedestrian facilities, cycling facilities, the presence of green open space, and security are considered to be less in rental housing areas compared to owned housing.